STRUCTURAL ANALYSIS OF THE COSTS AND THEIR EFFICIENCY INMARITSA-IZTOK 2 TPP EAD FOR THE PERIOD 2013-2022. - Kolev, Rosen (E-Journal VFU, 2024)
The energy crisis on a global scale due to both the economic difficulties caused by COVID-19 and the lack of resources related to the war in Ukraine has led to a shortage of electricity in the European free markets. Restrictions related to the Kyoto document and environmental pollution imposed in the European Union predetermine the closure of a number of coal plants. The economic situation in the last two years has shown that neither 155 globally nor at the European level are industries ready to abandon the use of electricity from sources that pollute the environment. The production of electricity in Bulgaria is highly dependent on thermal power plants, and they have been producing and placing record amounts of electricity on the free markets in recent years. An attempt has been made to highlight the importance of TPP "Maritsa-Iztok 2" EAD for the energy balance and national security in the Republic of Bulgaria.